Agar media for isolation of Neonectria ditissima from symptomatic and asymptomatic apple tissues and production of infective conidia - Amponsah, N.T.; Walter, M.; Scheper, R.W.A. (New Zealand Plant Protection, 2014)
European canker pathogen caused by the fungus Neonectria ditissima could not be isolated when infected woody tissues were plated directly onto potato dextrose agar (PDA) malt extract agar (MEA) or acidified PDA (pH 45) However the alternative media water agar (WA) and apple sapamended water agar (ASAWA) were successfully used to isolate the pathogen In the preparation of ASAWA green shoots of 1yearold fresh Scilate apple were frozen overnight then allowed to thaw The tissues were then centrifuged and the sap collected to prepare the medium Neonectria ditissima could be isolated from both symptomatic and asymptomatic apple tissues on both WA and ASAWA Both media supported the production of large numbers of conidia in vitro with more conidia being produced on ASAWA than on WA The conidia produced in vitro had morphological characteristics and pathogenicity similar to those produced in the field